2022
DOI: 10.1016/s2542-5196(21)00277-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to low ambient air pollution concentrations and mortality among 28 million people: results from seven large European cohorts within the ELAPSE project

Abstract: Background Long-term exposure to ambient air pollution has been associated with premature mortality, but associations at concentrations lower than current annual limit values are uncertain. We analysed associations between low-level air pollution and mortality within the multicentre study Effects of Low-Level Air Pollution: A Study in Europe (ELAPSE). MethodsIn this multicentre longitudinal study, we analysed seven population-based cohorts of adults (age ≥30 years) within ELAPSE,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
86
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(93 citation statements)
references
References 34 publications
6
86
0
1
Order By: Relevance
“…After detailed scrutinization of the remaining 272 studies, a total of 25 studies concerning long-term O 3 exposure and multi-cause mortalities were included for quality evaluation, meta-analysis, and further discussions ( Figure 1 ). 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Table 1 summarizes the basic information of the 25 included studies sorted by the publication year and surname of the first author, and Table S3 lists the key confounders adjusted in each study.
Figure 1 Schematic flowchart of study assessment and selection processes for literature review and meta-analysis
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After detailed scrutinization of the remaining 272 studies, a total of 25 studies concerning long-term O 3 exposure and multi-cause mortalities were included for quality evaluation, meta-analysis, and further discussions ( Figure 1 ). 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Table 1 summarizes the basic information of the 25 included studies sorted by the publication year and surname of the first author, and Table S3 lists the key confounders adjusted in each study.
Figure 1 Schematic flowchart of study assessment and selection processes for literature review and meta-analysis
…”
Section: Resultsmentioning
confidence: 99%
“…2022 61 BC2001 Belgium 2001–2011 general 5,474,470 FM ≥30 AC, RESP, CVD, LC Stafoggia et al. 2022 62 ELAPSE seven countries d 2000–2017 general 28,153,138 FM ≥30 AC, RESP, CVD, LC Cohort abbreviations: AHSMOG, Adventist Health Study of Smog ; WU-EPRI, Washington University–Electric Power Research Institute ; ACS CPS, American Cancer Society Cancer Prevention Study ; CTS, California Teacher Study ; CPRD, Clinical Practice Research Datalink ; GAZEL, GAZ de France and ÉLectricité ; CANCHEC, Canadian Census Health and Environment Cohort ; MINAP, Myocardial Ischaemia National Audit Project ; DDCH, Danish Diet, Cancer and Health ; NIH-AARP, National Institute of Health, American Association of Retired Persons ; ONPHEC, Ontario Population Health and Environment Cohort ; BC2001, Belgian 2001 Census . Key confounding adjustments were listed in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After detailed scrutinisation for 272 studies, a total of 25 studies concerning long-term O 3 exposure and multi-cause mortalities were finally enrolled for quality evaluation, meta-analysis and further discussions ( Figure 1 ). 38-62 Table 1 summarised the basic information of the 25 included studies sorted by the publication year and surname of the first author.…”
Section: Resultsmentioning
confidence: 99%
“…They reported identical effect estimates for the two continents, namely 1.03 [95% confidence interval (CI): 1.02, 1.03] and 1.03 (95% CI: 1.01, 1.04) per , respectively. In addition, the latest report 5 from the large Effects of Low-Level Air Pollution: A Study in Europe (ELAPSE) project in Europe showed that adjusting for fine particulate matter ( ), black carbon, and ozone did not alter the effect estimate of on mortality: single pollutant 1.044 (95% CI: 1.019, 1.069); with , 1.042 (95% CI: 1.020, 1.065); with black carbon, 1.041 (95% CIL 1.009, 1.073); and with ozone, 1.040 (95% CI: 1.012, 1.069). This evidence suggests that is not merely an indicator of other pollutants from diesel exhaust.…”
mentioning
confidence: 99%